OPERATIONAL & MAINTENANCE COST AND REVENUE ANALYSIS ON THE CONCEPTUAL DESIGN OF BATUAMPAR CARGO PORT SYSTEMS OF BATAM CITY USING VALUEENGINEERING APPROACH - Edi Indera, Yelna Yuristiary, Chablullah Wibisono, Tri Nadya Pratiwi (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
BatuAmparBatam Port is a large port; besides serving general goods, it also serves loading and unloading containers. The volume of goods shipments through the BatuAmpar Port continues to increase from year to year. Besides, its use is also expected to increase the number of loads that can be handled. There needs to be an increase in the addition of functions and investment analysis for the long term to lure investors to come. Based on this phenomenon, research with the title Operational & Maintenance Cost and Revenue Analysis on the Conceptual Design of the BatuAmparBatam Cargo Port System with a Value Engineering Approach needs to be carried out. Before conducting a conceptual design, a project feasibility study is required to see an investment's feasibility. This study aims to analyze the feasibility of infrastructure using the Value Engineering method by considering the components of container terminals, cargo building, dry bulk, breakbulk, liquid measurement, passenger ports, railway systems, and income from 2018-2068. The cost analysis was obtained from the results of benchmarking to several countries.